Heartland Serial Killers : Belle Gunness, Johann Hoch, and Murder for Profit in Gaslight Era Chicago - Lindberg, Richard C., 1953- (Book collections on Project MUSE., 2011)
"The chilling true story of two turn-of-the-century serial killers, Belle Gunness and Johann Hoch"--Provided by publisher.